KREATIVITAS ABDUL GAFAR DALAM MENCIPTAKAN LAGU POP DAERAH SUMBAWA NUSA TENGGARA BARAT - Risky Asriana Jaelani; Rivaldi Ihsan (STRETTO: Jurnal Penyajian, Pengkajian dan Penciptaan Musik, 2023)
This article discusses the creativity of Abdul Gafar, known as Apang, a person who created regional pop songs from Sumbawa, West Nusa Tenggara. Apang, a musician from Sumbawa Besar, is not only a songwriter but also a solo organ player who still exists in the Sumbawa area and its surroundings. His works have succeeded in penetrating the market and competing with other songs in Sumbawa Regency, as well as making a positive contribution to the local music industry. This research applies Rhodes' four "P" concept, as explained by Utami Munandar, to analyze Apang's creative values in creating regional pop songs. Aspects such as person, process, driving factors and results are analyzed in depth. The research results show that Apang is a creative individual with a structured creative process. The focus of the research involves understanding the creative process in song creation and identifying the distinctive characteristics of Apang's songs. These findings indicate that the songs resulting from Apang's creativity have distinctive characteristics and characteristics in the application of song lyrics originating from the Samawa ethnic language, as well as harmonies that adapt to their musical characteristics which differentiate them from other musical works in the music industry.